Evaluation of a Cryptococcal antigen Lateral Flow Assay in serum and cerebrospinal fluid for rapid diagnosis of cryptococcosis in Colombia (2017)
ABSTRACT : A Lateral Flow Assay to detect cryptococcal antigen (CrAg® LFA) in serum and cerebrospinal fluid for the rapid diagnosis of cryptococcosis was evaluated. A retrospective validation was performed. Sensitivity and specificity of the CrAg® LFA was 100%. High concordance (kappa index=1.0) between Cryptococcal Antigen Latex Agglutination System (CALAS®) and CrAg® LFA was observed. CrAg® LFA showed higher analytical sensitivity for detecting low concentrations of cryptococcal antigen.